ANALISIS KRITERIA KAMAR KOS LAYAK HUNI MENGGUNAKAN ALGORITMA C4.5 DI KOTA BATAM - Hutagalung, Ratih yuninda; Rika Harman, S.Kom., M.SI. (Computer Science and Industrial Engineering, 2023)
ABSTRACT Comfort residence is a basic human need. A sense of comfort and security is a benchmark for decent housing. It is said to be appropriate if the rented room meets the eligibility standards according to the occupants, starting from the drains, toilets, air ventilation, room size and according to the price given. To find out whether a boarding room/dormitory is feasible, the authors find a solution using the C4.5 algorithm. This study also uses the WEKA application version 3.9. The researchers distributed questionnaires to 70 boarding house occupants after which the data received would be processed through a manual counting process and entered into tabulations and according to the variables then tested again with the WEKA application to adjust the correctness of the data. Writer used 2 decision variables, namely Decent and Undecent.